2006
DOI: 10.1186/1477-7525-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and pain in premenopausal women with major depressive disorder: The POWER Study

Abstract: Background: Whereas it is established that organic pain may induce depression, it is unclear whether pain is more common in healthy subjects with depression. We assessed the prevalence of pain in premenopausal women with major depression (MDD). Subjects were 21-to 45-year-old premenopausal women with MDD (N = 70; age: 35.4 +/-6.6; mean +/-SD) and healthy matched controls (N = 36; age 35.4 +/-6.4) participating in a study of bone turnover, the P.O.W.E.R. (Premenopausal, Osteopenia/Osteoporosis, Women, Alendrona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 24 publications
3
22
0
1
Order By: Relevance
“…However, Beauchamp et al reported that physician ratings of asthenopia were correlated with patient-reported willingness to trade life expectancy to be rid of strabismus. 22 Depression is associated with more intense pain symptoms, 23, 24 and it is possible that the strabismic patients reported more ocular pain due to the higher prevalence of depressive symptoms in this group. Our results suggest that ocular pain may play a more important role in quality of life in strabismic patients than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…However, Beauchamp et al reported that physician ratings of asthenopia were correlated with patient-reported willingness to trade life expectancy to be rid of strabismus. 22 Depression is associated with more intense pain symptoms, 23, 24 and it is possible that the strabismic patients reported more ocular pain due to the higher prevalence of depressive symptoms in this group. Our results suggest that ocular pain may play a more important role in quality of life in strabismic patients than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, from the point of view of the aetiology, it can be divided in organic, psycho-social, or mixed [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that calcitonin reduces pain by acting on the central nervous system by modulating the serotonergic system [30,31] and selective estrogen receptor modifiers by affecting the sensitivity of nociceptive receptors or the endogenous opioid pathway system [32,33]. The mechanism by which bisphosphonates relieve pain remains unclear; however, some explanations have been suggested: (1) suppression of bone resorption and prevention of microfractures in the trabeculae of the spine and (2) reduction of prostaglandins and cytokines [9,34,35].…”
Section: Discussionmentioning
confidence: 93%